Clinical impact of regression from sustained to paroxysmal atrial fibrillation: the Fushimi AF registry. (25th November 2020) - Fujino, A; Ogawa, H; Ikeda, S; Doi, K; Hamatani, Y; An, Y; Ishii, M; Iguchi, M; Masunaga, N; Esato, M; Tsuji, H; Wada, H; et al.
Abstract: Background: Atrial fibrillation (AF) commonly progresses from paroxysmal type to sustained type in the natural course of the disease, and we previously demonstrated that the progression of AF was associated with increased risk of clinical adverse events. There are some patients, though less frequently, who regress from sustained to paroxysmal AF, but the clinical impact of the regression of AF remains unknown. Purpose: We sought to investigate whether regression from sustained to paroxysmal AF is associated with better clinical outcomes. Methods: Using the dataset of the Fushimi AF Registry, patients who were diagnosed as sustained (persistent or permanent) AF at baseline were studied. Conversion of sustained AF to paroxysmal AF during follow-up was defined as regression of AF. Major adverse cardiac events (MACE) were defined as the composite of cardiac death, stroke, and hospitalization for heart failure (HF). Event rates were compared between the patients with and without regression of AF. In patients with sustained AF at baseline, predictors of MACE were identified using Cox proportional hazards model. Results: Among 2, 253 patients who were diagnosed as sustained AF at baseline, regression of AF was observed in 9.0% (202/2, 253, 2.0 per 100 patient-years) during a median follow-up of 4.0 years. Of these, 24.3% (49/202, 4.6 per 100 patient-years) of the patients finally recurred to sustained AF during follow-up. The proportion of asymptomatic patients was lower in patients with regression of AF than those without (with vs without regression; 49.0% vs 69.5%, p<0.01). The percentage of beta-blocker use at baseline was similar between the two groups (37.2% vs 33.8%, p=0.34). The prevalence of patients who underwent catheter ablation or electrical cardioversion during follow-up was higher in patients with regression of AF (catheter ablation: 15.8% vs 5.5%; p<0.01, cardioversion: 4.0% vs 1.4%; p<0.01, respectively). The rate of MACE was significantly lower in patients with regression of AF as compared with patients who maintained sustained AF (3.7 vs 6.2 per 100 patient-years, log-rank p<0.01). Figure shows the Kaplan-Meier curves for MACE, cardiac death, hospitalization for heart failure, and stroke. In patients with sustained AF at baseline, multivariable Cox proportional hazards model demonstrated that regression of AF was an independent predictor of lower MACE (adjusted hazard ratio [HR]: 0.50, 95% confidence interval [CI]: 0.28 to 0.88, p=0.02), stroke (HR: 0.51, 95% CI: 0.30 to 0.88, p=0.02), and hospitalization for HF (HR: 0.50, 95% CI: 0.29 to 0.85, p=0.01). Conclusion: Regression from sustained to paroxysmal AF was associated with a lower incidence of adverse cardiac events. Funding Acknowledgement: Type of funding source: None